DAMPAK PROJECT-BASED LEARNING BERBANTUAN POSTER TERHADAP KREATIVITAS BELAJAR SISWA DALAM PENDIDIKAN PANCASILA: STUDI KUASI-EKSPERIMENTAL - Ainun Hidayah; Edy Herianto; Ahmad Hudori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examined the impact of poster-assisted Project-Based Learning on students’ learning creativity in Pancasila Education. A quantitative approach was employed using a quasi-experimental nonequivalent control group design. The population comprised 202 eighth-grade students at SMPN 2 Kuripan. The sample included 68 students selected through purposive sampling, with 34 students assigned to the experimental class and 34 to the control class. The experimental class participated in project-based learning activities that produced posters, while the control class received conventional instruction. Data were collected using a 47-item learning creativity questionnaire that met validity requirements and achieved a Cronbach’s Alpha reliability coefficient of 0.912. The data were analyzed using descriptive statistics, normality and homogeneity tests, and Analysis of Covariance, with pretest scores treated as the covariate. The experimental class mean increased from 68.78 to 86.59, whereas the control class mean increased from 64.72 to 69.83. ANCOVA results indicated a significant difference between the groups after controlling for ability, F(1,65)=87.722, p<0.001, with a partial eta squared of 0.574. These findings demonstrate that poster-assisted Project-Based Learning enhances learning creativity through idea exploration, collaboration, concept visualization, project completion, and presentation of work. This model supports active, creative, contextual, sustainable, and student-centered Pancasila Education for future learning.